2021
DOI: 10.1002/lpor.202000516
|View full text |Cite
|
Sign up to set email alerts
|

Directional Coupling of Emitters into Waveguides: A Symmetry Perspective

Abstract: Recent experiments demonstrate strongly directional coupling of light into waveguide modes. Here, the symmetry mechanisms behind this effect are studied, and it is shown that the analysis of the symmetries and symmetry‐breakings of the emitter‐waveguide system allows to qualitatively understand directional coupling in several situations. The authors consider emitters either centered in a median plane of the waveguide, or displaced from it, and whose emissions have a well‐defined angular momentum in either one … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…3 [4]): Translational symmetry in focusing, and electromagnetic duality symmetry (see below) in scattering. For the directional coupling of emitters onto waveguides, it is readily shown that the polarization handedness of the emission cannot be responsible for the directionality, which is controlled by angular momentum [5], see Fig. 3.…”
Section: Fundamentals and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 [4]): Translational symmetry in focusing, and electromagnetic duality symmetry (see below) in scattering. For the directional coupling of emitters onto waveguides, it is readily shown that the polarization handedness of the emission cannot be responsible for the directionality, which is controlled by angular momentum [5], see Fig. 3.…”
Section: Fundamentals and Applicationsmentioning
confidence: 99%
“…for a real angle θ, and its action on the helical fields F λ (r,t) → F θ λ (r,t) = F λ (r,t) exp(-λiθ) (5) reveals that, in the same way that rotations are generated by angular momentum operators, e.g. R z (θ) = exp(-iθJ z ), duality is generated by the helicity operator D θ = exp(-iθΛ).…”
Section: Fundamentals and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3,15–19 ] In general, it is achieved through the judicious design of either asymmetric waveguide structures [ 20–22 ] or complex excitation sources, [ 7,23–28 ] such as the extensively studied circularly polarized dipoles. Circular electric (magnetic) dipoles [ 5,25,29–31 ] are featured with a spinning electric (magnetic) dipole moment. Correspondingly, their near‐field directionality is determined by the spin‐momentum locking and can be understood from the perspective of quantum spin Hall effect of light.…”
Section: Introductionmentioning
confidence: 99%